1962
DOI: 10.1071/bi9620483
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Conidia of Peronospora Tabacina Adam I. Germination in Vitro

Abstract: SummaryWashed conidia of Perono8pora tabacina Adam germinated poorly or not at all in water alone, but germinated in the presence of riboflavin. The rate of germination of conidia in liquid suspension was enhanced by the presence of carbon and nitrogen sources, phosphate, and calcium and magnesium ions. The effects of 141 metabolites on germination and germ-tube elongation have been tested.A number of analogues of natural metabolites were inhibitory to germination and germ-tube elongation. Extracts and exudate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

1964
1964
1990
1990

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 8 publications
2
35
1
Order By: Relevance
“…In view of the effect of riboflavin on conidial germination shown by Shepherd (1962) it is interesting to note that in the present study ribofiavin itself has a significant stimulating effect on sporulation intensity (116·4% of the untreated control), the mononucleotide a greater effect (148·4%), and FAD the largest effect (173· 9%), which suggests the possible conversion of ribofiavin to FAD in the sporulating system.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In view of the effect of riboflavin on conidial germination shown by Shepherd (1962) it is interesting to note that in the present study ribofiavin itself has a significant stimulating effect on sporulation intensity (116·4% of the untreated control), the mononucleotide a greater effect (148·4%), and FAD the largest effect (173· 9%), which suggests the possible conversion of ribofiavin to FAD in the sporulating system.…”
Section: Discussionmentioning
confidence: 82%
“…Previously Shepherd (1962) suggested that uracil synthesis is limiting during the phase of germ-tube elongation. Xanthine, its analogues, and the related compounds caffeine and theophylline all show some degree of inhibition of sporulation, but the mechanism of this inhibition is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations